Motyw podróży w czasie w grach cyfrowych – podstawowe typy mechanik - Czyżak, Krzysztof (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
This article is an attempt to describe the ways in which the theme of time travel functions in video games. The text presents the two most common types of incorporating time travel into game mechanics. In the first type, an avatar has the ability to manipulate gameworld time. In the second case, time travel is simulated by a transfer of the avatar into a different game area. The article constitutes a step towards more advanced research on time travel in video games.